PRIORITY AREAS OF THE USSR STATE NATIONAL POLICY IN THE 1960s – 1980s - BUGAY, N.F. (Kavkazologiya, 2020)
The article examines the problems of the implementation of state ethnic policy in one of the most difficult periods of Soviet history. It was in the 1960s and 1980s that difficulties in interaction between the center and the national regions of the country manifested themselves, and the impact of the consequences of the prevalence of the personified factor in national politics was felt. Considerable attention is paid to the analysis of events on the territory of the North Caucasus region, where the specificity of the national policy was clearly manifested, expressed in the nature of the measures carried out by the center in this area. There was a process of developing new social technologies for its implementation in order to harmonize interethnic relations. Social issues related to the correction of mistakes of the past, first of all, the consequences of forced relocations of ethnic groups of the population and entire peoples, have acquired priority importance. This violated, in particular, the foundations of nation-building worked out by the peoples’ creativity. During the period under study, the forms and methods of interaction of citizens with the bodies of party and Soviet power changed significantly, the political system was improved. The state of the economic sector of the nation has become an independent factor influencing the social and political life of the multinational community. The lessons of ideological and political work on the solution of such a cardinal task as the formation of the “Soviet people” community require a new understanding. This concept reflected not only the ideological and political conjuncture of the early 1970s, in fact it took half a century of development to make possible official statement of its implementation. At the same time, during this period, the dynamism of the reforms that was observed in this sphere of social life in the 1920s was lost, and the established "model" of its development was losing its significance. Society felt the need to modernize many aspects of the sphere of interethnic relations. An example of the implementation of these measures was the North Caucasian region (restoration of national state formations, solution of territorial problems, improvement of the management system, implementation of a set of measures to implement new social technologies to manage national processes, appeal to the positive practices of the past in the implementation of transformations, consolidation of citizens based on constructive tasks). By no means all plans for the development of Soviet society were implemented during the period under review, which to a certain extent explains its further fate.